Synthesis and Evaluation of Novel Xanthone Derivatives as Potent Dipeptidyl Peptidase-4 Inhibitors - Ren, Haixiang; Zhuo, Xiaobin; Su, Hua; Li, Xiang; Tang, Hao; Jin, Yongshen; Zhao, Qingjie; Wang, Shudong (Asian Journal of Chemistry, 2015)
Two series of xanthone derivatives have been designed, synthesized and evaluated as potent dipeptidyl peptidase-4 inhibitors and among them seven compounds were firstly reported. Most of the inhibitors showed moderate inhibitory activities aganist dipeptidyl peptidase-4 and compounds 2a, 2c, 2d, 2f and 2g exhibited potent activities against dipeptidyl peptidase-4 compared with the positive control diprotin A.